Integrative analysis of m6A-SNPs and single-cell RNA sequencing reveals key drivers of endocrine combined with CDK4/6 inhibitor therapy resistance in ER+ breast cancer - Ming, Ruijie; Zhang, Han; Wu, Huan; Zhan, Fangbiao; Huang, Xiaoping; Liu, Huawen (Frontiers in Pharmacology, 2025)
BackgroundEndocrine therapy combined with CDK4/6 inhibitors remains a standard treatment for ER+ breast cancer, yet resistance is a prevalent challenge. This study explores the role of N6-methyladenosine (m6A) modifications, influenced by m6A-SNPs, in shaping therapy resistance, utilizing single-cell RNA sequencing to delineate the underlying molecular mechanisms.MethodsWe integrated genome-wide association study data with single-cell transcriptomic profiles from ER+ breast cancer patients, focusing on differences between resistant and sensitive responses to CDK4/6 inhibitors. m6A-SNPs were identified and analyzed for their impact on gene expression and interactions with RNA-binding proteins, with a particular focus on their roles within key cellular pathways.ResultsThe study identified crucial m6A-SNPs associated with therapy resistance. Notably, changes in the expression of FILIP1L and TOM1L1, related to these SNPs, were mapped using pseudotime trajectory analysis, which traced the evolution from sensitive to resistant cellular states. FILIP1L and TOM1L1 exhibited dynamic expression changes along the trajectory, correlating with significant shifts in cell fate decisions. These findings underscore their potential roles as mediators in the development of resistance, particularly through their involvement in the PI3K-Akt and Wnt signaling pathways, critical in cancer progression and drug resistance.ConclusionOur findings emphasize the importance of m6A-SNPs in influencing resistance to therapy in ER+ breast cancer. The dynamic regulation of FILIP1L and TOM1L1 along the developmental trajectory of tumor cells from sensitivity to resistance provides insights into the molecular complexity of therapy resistance. These results pave the way for developing targeted therapies that modify m6A-driven pathways, offering new strategies to counteract resistance and improve patient outcomes.